Thermal effects on the synthesis of 1,1-dibutoxyethane in a fixed-bed adsorptive reactor - Graça, Nuno S. (2014)
The effects of temperature on the synthesis of 1,1-dibutoxyethane (DBE) in a fixedbed adsorptive reactor were studied by performing both adsorption/desorption and reaction/regeneration experiments at 15 and 35 °C. The Langmuir-type isotherm parameters at 15 and 35 °C were obtained from the adsorption/desorption experiments. The reaction/regeneration experiments showed an increase in both conversion and productivity with increasing temperature. Isothermal and nonisothermal mathematical models were used to simulate the reactor operation with different Damköhler numbers. The simulated results suggest that the reactor productivity can be improved by using the adiabatic operation mode on the fixedbed adsorptive reactor, obtaining a productivity for DBE of 71.8 mol kg–1h–1.